2014
DOI: 10.1002/elan.201400107
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Cathodic Stripping Voltammetric Determination of Uranium(VI) in Presence of N‐Phenylanthranilic Acid

Abstract: N‐Phenylanthranilic acid was used as a complexing agent for determination of uranium(VI) by adsorptive cathodic stripping voltammetry. Under the optimal experimental conditions of the experimental parameters, the peak current was proportional to the concentration of U(VI) in the range 0.75–30 ng mL−1 and the detection limit was 0.036 ng mL−1. The influence of possible interferences was investigated. The method was applied for determination of uranium in waste water from uranium conversion facility and natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…It should be clearly indicated that for the shortest analysis time the proposed sensor allows to obtained the lowest limits of detection and quantification compared to all other sensors. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]46 Additionally, for the first time, the proposed sensor can be applied in portable analyzer, which enables us to perform field analysis of U(VI) in concentrations that actually occur in environmental water samples. Furthermore, the obtained limit of detection is significantly lower than obtained for another techniques applied for uranium determination in environmental samples: 2.4 nmol L −1 and 1.8 nmol L −1 for ICP-OES, 12,13 210 nmol L −1 for ICP-MS, 14 2.5 nmol L −1 for spectrophotometry 17 and 0.13 nmol L −1 for fluorometric determination of uranium.…”
Section: Optimization Of Lead Film Plating and U(vi) Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be clearly indicated that for the shortest analysis time the proposed sensor allows to obtained the lowest limits of detection and quantification compared to all other sensors. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]46 Additionally, for the first time, the proposed sensor can be applied in portable analyzer, which enables us to perform field analysis of U(VI) in concentrations that actually occur in environmental water samples. Furthermore, the obtained limit of detection is significantly lower than obtained for another techniques applied for uranium determination in environmental samples: 2.4 nmol L −1 and 1.8 nmol L −1 for ICP-OES, 12,13 210 nmol L −1 for ICP-MS, 14 2.5 nmol L −1 for spectrophotometry 17 and 0.13 nmol L −1 for fluorometric determination of uranium.…”
Section: Optimization Of Lead Film Plating and U(vi) Determinationmentioning
confidence: 99%
“…23 One of the most popular sensors involved for uranium determination is the hanging mercury drop electrode (HMDE), which has a lot of advantages, but it is rarely applied because of volatility and toxicity of mercury. [24][25][26][27][28][29][30] Examples of alternative electrodes used for uranium quantification were: double electrode system, where the first electrode was modified with lead glassy carbon electrode (GCE) with a large surface area and the second was an ensemble of five carbon composite microelectrodes also modified with lead, glassy carbon electrodes modified in situ with various metals: bismuth, mercury and lead or ex situ bismuth-coated GCE. [31][32][33][34][35][36] Moreover, other modified sensors were also applied: polymer coated glassy carbon electrode obtained by electropolymerization z E-mail: ktyszczuk@poczta.umcs.lublin.pl of N-phenylanthranilic acid and carbon nanotube-modified GCE.…”
mentioning
confidence: 99%